Autosomal recessive Noonan syndrome associated with biallelic LZTR1 variants. (October 2018) - Johnston, Jennifer; van der Smagt, Jasper; Rosenfeld, Jill; Pagnamenta, Alistair; Alswaid, Abdulrahman; Baker, Eva; Blair, Edward; Borck, Guntram; Brinkmann, Julia; Craigen, William; Dung, Vu Chi; Emrick, Lisa; et al.
Abstract Purpose To characterize the molecular genetics of autosomal recessive Noonan syndrome. Methods Families underwent phenotyping for features of Noonan syndrome in children and their parents. Two multiplex families underwent linkage analysis. Exome, genome, or multigene panel sequencing was used to identify variants. The molecular consequences of observed splice variants were evaluated by reverse-transcription polymerase chain reaction. Results Twelve families with a total of 23 affected children with features of Noonan syndrome were evaluated. The phenotypic range included mildly affected patients, but it was lethal in some, with cardiac disease and leukemia. All of the parents were unaffected. Linkage analysis using a recessive model supported a candidate region in chromosome 22q11, which includesLZTR1, previously shown to harbor mutations in patients with Noonan syndrome inherited in a dominant pattern. Sequencing analyses of 21 live-born patients and a stillbirth identified biallelic pathogenic variants inLZTR1, including putative loss-of-function, missense, and canonical and noncanonical splicing variants in the affected children, with heterozygous, clinically unaffected parents and heterozygous or normal genotypes in unaffected siblings. Conclusion These clinical and genetic data confirm the existence of a form of Noonan syndrome that is inherited in an autosomal recessive pattern and identify biallelic mutations inLZTR1 .